2007
DOI: 10.1016/j.ijcard.2005.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Impaired health status in Type D patients following PCI in the drug-eluting stent era

Abstract: Background: Drug-eluting stenting reduces restenosis post-percutaneous coronary intervention (PCI), but subgroups of patients may not benefit optimally from this procedure. We examined the impact of Type D personality on health status over time and the clinical relevance of Type D as a predictor of impaired health status at 12 months in unselected post-PCI patients. Methods: Consecutive patients (n = 692) participating in the Rapamycin-Eluting Stent Evaluated At Rotterdam Cardiology Hospital (RESEARCH) registr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 35 publications
(38 reference statements)
4
36
0
2
Order By: Relevance
“…The findings of the current study are in line with previous studies in patients with peripheral arterial disease [13], treated with revascularization procedures [16,35], and patients with chronic heart failure [14], showing that Type D patients report poorer health status compared to non-Type D patients despite both personality taxonomies benefiting from medical treatment. In the present study, we found a non-significant interaction effect for Type D personality by time, indicating that personality did not moderate the effects of cardiac rehabilitation on health status but exerted a stable effect on health status over time.…”
Section: Discussionsupporting
confidence: 90%
“…The findings of the current study are in line with previous studies in patients with peripheral arterial disease [13], treated with revascularization procedures [16,35], and patients with chronic heart failure [14], showing that Type D patients report poorer health status compared to non-Type D patients despite both personality taxonomies benefiting from medical treatment. In the present study, we found a non-significant interaction effect for Type D personality by time, indicating that personality did not moderate the effects of cardiac rehabilitation on health status but exerted a stable effect on health status over time.…”
Section: Discussionsupporting
confidence: 90%
“…Given that this is the first study to find such a high prevalence in CVD patients in Type D research to date, this finding should be replicated in other Eastern European studies. Nevertheless, if such a high prevalence is confirmed in future research, with the prevalence in CVD patients being almost twice as high as in the general population, this might have serious implications for Polish CVD patients and their clinical and psychosocial management, as Type D has been related to increased mortality and morbidity in Western European studies Schiffer, Pedersen, Widdershoven, Hendriks, Winter & Denollet, 2005;Al-Ruzzeh, Athanasiou, Mangoush, Wray, Modine, George, et al, 2005;Pedersen, Denollet, Ong, Serruys, Erdman & van Domburg, 2007;Denollet, Vaes & Brutsaert, 2000;Denollet, Pedersen, Ong, Erdman, Serruys & van Domburg, 2006;Pedersen, Lemos, van Vooren, Liu, Daemen, Erdman et al, 2004).…”
Section: Discussionmentioning
confidence: 91%
“…Others have also recommended the use of the DS14 as one of the measures to use in clinical cardiology practice to identify high-risk patients (Albus, Jordan & HerrmannLingen, 2004), as Type D has been associated with adverse health outcomes, including increased risk of mortality and morbidity Schiffer, Pedersen, Widdershoven, Hendriks, Winter & Denollet, 2005;, AlRuzzeh, Athanasiou, Mangoush, Wray, Modine, George, et al, 2005;Pedersen, Denollet, Ong, Serruys, Erdman & van Domburg, 2007;Denollet, Vaes & Brutsaert, 2000;Denollet, Pedersen, Ong, Erdman, Serruys & van Domburg, 2006;Pedersen, Lemos, van Vooren, Liu, Daemen, Erdman et al, 2004). The use of the DS14 could also be extended to other diseases, as Type D has been shown to predict the onset of cancer in patients with CVD (Denollet, 1998), although further cross-cultural research into the predictive validity of the Type D construct in relation to clinical outcomes in other somatic diseases is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations